PENERAPAN PEMBELAJARAN THINK TALK WRITE (TTW) DENGAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Insani, Tiara Nur; Setiani, Ana; Balkist, Pujia Siti (Universitas Bhinneka PGRI, 2025)
This study is to compare the ability of junior high school students in solving mathematical problems between those who learn with the Think Talk Write (TTW) model using a contextual approach and those who learn through conventional models. The type of study applied is quantitative research with a quasi experimental approach that implements a pretest-posttest control group design. The research subjects were VIII grade students of SMP Negeri 1 Jampang Tengah with a total of 78 students. There were three classes used in this study, namely experimental class A, experimental class B, and control class. The instrument used was a test instrument. The analysis method applied involves the parametric test of Anava one lane unequal and post-anava test. The results of this study indicate that learning with the Think Talk Write (TTW) model assisted by a contextual approach is superior to the conventional model in terms of students' ability to solve mathematical problems.